Acute kidney injury after multiple cycles of cisplatin chemotherapy: A nomogram for risk assessment - Xuejing Zhu; Juanjuan Li; Yushang Tang; Xiaoping Li; Juntian Xu; Ran Jing; Tongqiang Liu (Karger Publishers, 2023)
Abstract Background: Acute kidney injury (AKI) caused by cisplatin is common and has a higher incidence of multiple use, resulting in a poor short- and long-term prognosis for patients. There is currently no good pre-medication AKI risk assessment tool. The aim of this study is to establish an AKI risk assessment nomogram for patients with multiple cisplatin applications. Methods: This study was a retrospective analysis of patients who were treated with non-first-time cisplatin chemotherapy regimen in Changzhou second people's Hospital affiliated to Nanjing Medical University from January 2016 to January 2022. All data of the development group were used to screen the impact factors of AKI via univariate and multivariate analyses. A nomogram was developed based on these impact factors and verified with verification group. The area under the curve (AUC) of receiver-operating characteristic (ROC) curve, calibration curves, and decision curve analyses (DCAs) were used to evaluate the nomogram. Results: Among the 256 patients enrolled in 450 cycles of chemotherapy, 282 were in the development cohort (97 AKI), and 168 were in the validation cohort (61 AKI). Multivariate logistic regression revealed that age, hypertension, diabetes, sCysC, uKim1 and a single dose of cisplatin were independently associated with AKI. The results showed that our model yielded satisfied diagnostic performance with an AUC value of 0.887 and 0.906 using the development group and on verification group. The calibration plots and DCA showed the superior clinical applicability of the nomogram. These results were verified in the validation cohort. Conclusion: A nomogram combining functional (sCysC) and tubular (uKim1) injury biomarkers with conventional clinical factors might assess the risk of AKI after multiple cycles of cisplatin chemotherapy.